What do German Molecular Tumor Boards recommend in patients with PIK3CA-mutated tumors?: Launch and first results from the German Transsectoral Molecular Tumor Board exchange platform Deutschland - Pretzell, Ina; Desuki, Alexander; Bleckmann, Annalen; Loges, Sonja; Reinacher-Schick, Anke; Westphalen, C. Benedikt; Lange, Sebastian (Oncology research and treatment, 2024)
Introduction: Comprehensive molecular tumor profiling is widely used in the management of patients with cancer. Molecular tumor boards devise treatment strategies based on testing results. In this setting, the Transsectoral Molecular Tumor Board exchange platform Deutschland (TEAM-D) aims to drive peer-to-peer exchange to connect experts in the field. Methods: During the first virtual TEAM-D meeting, participants from 16 German universities and 5 nonacademic institutions discussed five cases with PIK3CA hotspot mutations. Furthermore, an illustrative case vignette was presented. Results: Overall, German caregivers show restraint in administering off-label PIK3CA inhibitor and favor clinical trials in this setting. Conclusion: In the setting of precision oncology, TEAM-D enables virtual case discussion across the different sectors of the German healthcare system. Based on the example of PIK3CA hotspot mutations, TEAM-D demonstrated the value of integrating knowledge from different healthcare professionals.